US Army blood program: 2025 and beyond. (March 2016) - Gonzales, Richard; Taylor, Audra L.; Atkinson, Andrew J.; Malloy, Wilbur W.; Macdonald, Victor W.; Cap, Andrew P.
Abstract : In preparing to support the Army in 2025 and beyond, the Army Blood Program remains actively engaged with the research and advanced development of blood products and medical technology to improve blood safety and efficacy in conjunction with the US Army Medical Research and Materiel Command. National and International Blood Bank authorities have noted that the US Army research and development efforts in providing new blood products and improving blood safety operate on the cutting edge of technology and are transformational for the global blood industry. Over the past 14 years, the Army has transformed how blood support is provided and improved the survival rate of casualties. Almost every product or process developed by or for the military has found an application in treating civilian patients. Conflicts have many unwanted consequences; however, in times of conflict, one positive aspect is the identification of novel solutions to improve the safety and efficacy of the blood supply.